Analysis The Effectiveness Of Tax Relaxation Due To Covid-19 Pandemy On Indonesian Economic Defense - Munandar, Mutiara Hamdalah (Universitas Negeri Semarang, 2020)
The Act Number 28 of 2007 concerning General Provisions and Tax Procedures, it is explained that tax is a mandatory contribution to the state owed by individuals or entities that are forcing based on the law, with no direct compensation and is used for state purposes for the magnitude of people's prosperity. Indonesia began to impose taxes with a self assessment system or trust to calculate tax payable, pay off tax shortages, calculate taxes paid, and report to the Directorate General of Taxes themselves. On March 13, 2020, the Ministry of Finance said that income tax relaxation would be imposed. The government has issued Regulation of the Minister of Finance (PMK) number 23 / PMK.03 / 2020, regarding Tax Incentives for Taxpayers affected by Corona Virus. However, is this effective? What is the impact of this relaxation policy on Indonesia's economic defense?